Independent and dynamic manipulation of surface waves radiation for quadruplex polarization channels enabled by programmable coding metasurface - Wang Zhenxu; Liu Tonghao; Liang Jian-Gang; Wang Jiafu; Meng Yueyu; Fu Xinmin; Chen Hongya; Zhu Ruichao; Chu Zuntian; Cui Yina; Sun Huiting; Wang Shaojie; et al. (Nanophotonics)
Flexible manipulation of surface waves (SWs) radiation has been continuously intriguing enormous interests of researchers due to its promising application prospects, and metasurfaces exhibit unparalleled capability to efficiently control SWs radiation. However, existing schemes still suffer from the bottlenecks of single radiation channel and immutable radiation pattern, which are difficult to satisfy the requirements of high-integration intelligent metadevices. Herein, an ingenious strategy of the SWs radiation metadevice is proposed to independently and dynamically manipulate SWs directional radiation in four polarization channels. The waveguide port and the guided wave structure are designed to excite and propagate the desired SWs, and the programmable coding metasurface can independently convert SWs into x-polarized radiation waves, y-polarized radiation waves, left-handed circular polarized radiation waves and right-handed circular polarized radiation waves and dynamically control the corresponding radiation angles by adjusting the ON/OFF states of two positive-intrinsic-negative diodes in each spin-decoupled meta-atom. Numerous simulation and experimental results of the proof-of-concept prototype are in good agreement with the theoretical predictions, which verify the feasibility of our proposed methodology. The innovative design of four-channel SWs radiation metadevice with high radiation efficiency and broad radiation bandwidth offers an excellent platform for flexibly manipulating SWs radiation, and possesses tremendous potential in engineering application.